Intranasal Dexmedetomidine for Sedation in Acute Ischemic Stroke: A Case Report - Antonio Romanelli; Antonella Langone; Flora Minichino; Renato Gammaldi (Journal of Neuroanaesthesiology and Critical Care)
This case report presents the innovative use of intranasal dexmedetomidine (IN-DEX) for sedation in an 82-year-old female patient undergoing endovascular treatment (EVT) for acute ischemic stroke (AIS). The patient, with a history of chronic atrial fibrillation, arterial hypertension, and chronic kidney failure, presented with sudden left-sided weakness. IN-DEX was administered to manage her agitation, achieving stable sedation without respiratory depression, facilitating EVT, and preserving the patient's cooperative state for accurate neurological assessments. The procedure was completed successfully, with stable vital parameters and no complications. This report highlights IN-DEX's potential as a noninvasive, effective sedative alternative in emergency neurological settings, emphasizing its advantages in maintaining respiratory function and reducing stress responses in AIS patients. Further studies are recommended to validate these findings and explore the broader applicability of IN-DEX in AIS management.